Sites of Anesthetic Block of the Lateral and Medial Palmar Metacarpal Nerves in Equines of Indeterminate Breed - Vieira, Tiago Machado; Riceti Magalhães, Henrique Inhauser; de Paula, Ygor Henrique; Romão, Fabiana Braz; Barcelos, Jeferson Borges; de Moura Guenka, Gabriela Soares; Ribeiro, Lucas de Assis; Carneiro e Silva, Frederico Ozanam (Acta Scientiae Veterinariae, 2019)
Background: Local anesthesia blockage at equines claudication diagnosis besides favoring the beginning of the therapy and relieving patient’s pain, it allows the identification of the specific affected region and its origin, however, if it is done incorrectly (by improper volume of anesthetics application and/or mistakenly nerve identification due to the lack of anatomic referential) it may cause inflammation, infection or even tissue necrosis. The aim was describing anatomically lateral and medial palmar metacarpal nerves in equines to improve diagnostic anesthetic block techniques on four metacarpophalangeal articulation joints of the specie. Materials, Methods & Results: A number of 20 thoracic limbs from 10 equines of indeterminate breed were used to be fixated in 10% phormaldehyde and with a marked arterial system by water solution of red dyed latex. The structures were identified by dissection, and their denomination bases on Nomina Anatomica Veterinaria (N.A.V.) by the International Committee on Veterinary Gross Anatomical Nomenclature. The study had been approved by the Board of Ethics in Animal Use of the University Center of Patos de Minas (UNIPAM), protocol n° 18/17. The lateral and medial palmar metacarpal nerves have been observed in all of the specimens originated from the deep branch of lateral palmar nerve, immediately distal to the intercarpal articulation. After its origin, the first nerve stretched ipsilaterally from the common trunk, whilst the second nerve positioned counter-lateral manner after superficially crossing the interosseus muscle. Both penetrated at the level of the mid third of the referred muscle and the metacarpal bone III and, assumed respectively a parallel medial position to the metacarpal bone IV and lateral to the metacarpal II, being intimately associated to the palmar face of the metacarpal bone III. Distally, those nerves emerged from a palmar position to a lateral and medial to the distal extremity of the metacarpal bones, corresponding and adjacent to the metacarpophalangeal articulation palmar recession, where they had finally ramified to partially innervate the associated articular capsule and the subcutaneous tissue of the region. Discussion: The lateral and medial palmar metacarpal nerves present similar origin and disposition to the above described, however, besides largely mentioned in literature, we point out here as recommended by N.A.V., no use of terms like axial and abaxial as position indicators for equine. As a part of block anesthetic diagnosis of four metacarpophalangeal articulation points, it is hereby suggested for the studied nerves desensitization, should be palpated the distal extremities of the metacarpal bones IV and II. After the identification, using thumb located from the extremity at proximal direction way, introduce the needle bilaterally for 1.5 cm downright between the above mentioned metacarpal bones and the interosseus muscle, being these latter and the flexor muscle tendons drawn in the palmar direction. Thus, it becomes valid to affirm that the technique of four-point diagnostic anesthetic block of the metacarpophalangeal articulation has been perfected for equines, and that it will limit the chances of false results on account of misplaced puncturing of nearby structures, such as, for example, the synovial recesses, mentioned as the location of the utmost gravity, hence septic synovitis may come in play.